FENOMENA MIGRASI SIRKULER DI KOTA MATARAM - SUNDARI, NI PUTU FEBBY; KARISMAWAN, PUTU; SALMAH, EMY (GANEC SWARA, 2020)
Theoretically, development of the city depends on labor resources. Generally, labor resources of the city come from periphery area. Developed infrastructure is a factor that mobilized labor resources from periphery to the city. There are two alternatives to the workers who come from periphery area; first they can stay in the city by renting apartment or the second as commuter. Many of the workers choose as commuter, so it is quite interesting to know what factors influence workers make choice as commuter. It is more specific whether factors such as income, length of work, age, distance, education level, and marital status influence the interest of workers to conduct circular migration. The analytical tool used is logistic regression analysis, Binary Regression Logistic. This research is a descriptive study that uses quantitative analysis using 1 dependent variable, namely interest in migration and six independent variables, namely income, length of working, age, distance, education level, and marital status. To achieve these objectives in this research logistic regression analysis was used, namely Binary Regression using primary data as many as 80 respondents. The results show that above variables; income, length of working, age, distance, level of education and marital status simultaneously and significantly influence on interest of workers in doing circulation migration to the Mataram City. Factors that partially influence significantly on the interest of workers doing migration to the Mataram City with a significance value with an alpha level of 5% are income, length of working, distance and level of education. While the age variable and marital status is not significant in effect.